Training on creating learning media for handling of disaster mitigation for elementary school teachers - Rachman, Indriyani; Murae, Fumitoshi; Kodama, Yayoi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Indonesia is known as a disaster-prone country, the total amount of damage due to disasters is said to be the fourth largest in the world. The impact of global warming results in very high rainfall and large-scale damage. Apart from weather disasters, a number of damages also occur due to geological disasters. To stop disaster damage in the long term, it is important to create sustainable communities. It is important not to separate the environment and disaster prevention, but to learn about the nature that sometimes threatens us just as we learn about the nature around us. Under these conditions, until now Indonesia has not included practical disaster education in the learning curriculum, because it is considered important to include disaster management training in school communities. Because of this, disaster management methods were tested in Japan, tested in elementary schools in the city of Mataram, Indonesia. This research aims to evaluate whether adapting traditional Japanese educational methods such as